Development theory and the economics of growth - Ros, Jaime (Ann Arbor : University of Michigan Press, 2000)
"The unifying theme of this book is that early theoretical insights and accumulated empirical knowledge of development economics have much to offer to research in the theoretical and empirical aspects of economic growth. With the help of a number of recent contributions, the ideas and insights of the classical literature in development economics can be given simple and rigorous formulations. Together, they amount to an approach to growth theory that can overcome the long-recognized empirical shortcomings of neoclassical growth economics, while being free from the objections that can be raised against the new brand of endogenous growth theory."--Jacket.
Includes index.
Includes bibliographical references (p. 405-419).
rpm 31/08/2016
Loans
Keywords: Development economics; Economic development